Growth of preterm low birth weight infants until 24 months corrected age: effect of maternal hypertension - Alice M. Kiy; Ligia M.S.S. Rugolo; Ana K.C. De Luca; José E. Corrente (Brazilian Society of Pediatrics, 2015)
Objective: To evaluate the growth pattern of low birth weight preterm infants born to hypertensive mothers, the occurrence of growth disorders, and risk factors for inadequate growth at 24 months of corrected age (CA). Methods: Cohort study of preterm low birth weight infants followed until 24 months CA, in a university hospital between January 2009 and December 2010. Inclusion criteria: gestational age < 37 weeks and birth weight of 1,500‐2,499 g. Exclusion criteria: multiple pregnancies, major congenital anomalies, and loss to follow up in the 2nd year of life. The following were evaluated: weight, length, and BMI. Outcomes: growth failure and risk of overweight at 0, 12, and 24 months CA. Student's t‐test, Repeated measures Anova (RM‐Anova), and multiple logistic regression were used. Results: A total of 80 preterm low birth weight infants born to hypertensive mothers and 101 born to normotensive mothers were studied. There was a higher risk of overweight in children of hypertensive mothers at 24 months; however, maternal hypertension was not a risk factor for inadequate growth. Logistic regression showed that being born small for gestational age and inadequate growth in the first 12 months of life were associated with poorer growth at 24 months. Conclusion: Preterm low birth weight born infants to hypertensive mothers have an increased risk of overweight at 24 months CA. Being born small for gestational age and inadequate growth in the 1st year of life are risk factors for growth disorders at 24 months CA.